Urgensi Pengakuan Dan Perlindungan Hukum Pers Mahasiswa Di Indonesia - M. Rizki Yudha Prawira (Jurnal Program Pascasarjana Ilmu Hukum Universitas Islam As-Syafi'iyah, 2023)
The Implementation of functions and journalistic works in Indonesia is not only carried out by the press as a legal entity, but also by so many student press organizations in Indonesia. The student press is one of the platforms for carrying out the functions of the press, which is often referred to as the fourth pillar of democracy. Unfortunately, the position of the student press in Indonesia is in a dilemma. First, there is no recognition in Law No. 40 of 1999 concerning the press, which makes it impossible to reach legal protection. Second, even though the recognition and provisions for journalistic activities are recognized as human rights and academic freedom, these provisions are not really able to guarantee their protection. Third, the dynamics of the problems faced by the student press are no doubt different from those with legal entities, such as threats of criminalization and attempts to ban them. This situation raises the urgency to revise the statutory provisions on the press or make a new regulation that specifically regulates the recognition and protection of the student press.